Cycle-skipping strategy with intake air cut off for natural gas fueled Si engine - Tuncer, Erdal; Sandalci, Tarkan; Pusat, Saban; Balci, Ozgun; Karagoz, Yasin (SAGE PUBLICATIONS LTD, 2021)
In this study, cycle-skipping was investigated for a natural gas engine which has single cylinder, unsupercharged with 1.16 L volume and spark ignition. Additionally, inlet manifold air was switched off during cycle-skipping to minimize pumping losses. Thus, cycle-skipping strategy was carried out, and its effects on emission and engine performance were investigated. Indicated mean effective pressure, indicated efficiency, specific emissions (CO, HC, and NOX) and combustion characteristics (in-cylinder pressure and rate of heat release) were investigated in the study. As a result of performed study, it is predicted that a significant improvement can be achieved in indicated thermal efficiency as 22.8% and 13.4% by different cycle-skipping strategies. However, there is not a continuous change in emissions for different cycle-skipping strategies. While CO and NOX emissions increased in 3N1S (three normal, one cycle-skip) condition, HC emissions decreased in accordance with normal condition. For both cycle-skipping strategies, all the emissions have an increase in accordance with normal condition. In 3N1S and 2N1S (two normal, one cycle-skip) cycle skip engine operating conditions, compared to engine operating under normal condition, CO emissions increased by 14.7 and 51.7 times, respectively. In terms of HC emissions, while emission values decreased by 27.8% under 3N1S operating conditions, they increased by 67.2% under 2N1S operating conditions. Finally, in 3N1S and 2N1S cycle skip engine operating conditions, NOx emissions increased by 3.7 and 6.9 times, respectively, compared to normal operating condition. Another significant result of this study is that peak in-cylinder pressure increased as the cycle-skipping rate increased.
Keywords: Cycle-skipping; natural gas; spark ignition engine; emissions; fuel consumption; SPARK-IGNITION ENGINES; CYLINDER-DEACTIVATION; VALVE; OPTIMIZATION; PERFORMANCE; Education & Educational Research; Science & Technology - Other Topics